The influence of brand experience and brand trust on brand loyalty mediated by brand love (a survey of eiger consumers in Purworejo Regency) - Dini Suci Ningtyas; Titin Ekowati; Dedi Runanto (International Journal of Applied Finance and Business Studies, 2025)
Outdoor adventure activities have increasingly become a popular hobby today, including exploring mountains, lakes, rivers, beaches, and other natural landscapes. Many people are attracted to various adventure activities such as hiking, riding, running, shooting, traveling, climbing, cycling, and others, which aim to enjoy natural beauty, test adrenaline, and improve physical fitness. In Indonesia’s current era of rapid modernization, competition in the outdoor product industry has become increasingly competitive, raising concerns among companies regarding their business sustainability—whether the products they manufacture can be accepted by consumers and whether their business can survive amid the intensifying market competition. Eiger is one of Indonesia’s local brands that has established a strong reputation in the outdoor and adventure equipment market. The rise of numerous local brands offering outdoor activity products has increased market competition, prompting companies to analyze the factors that may foster brand love, which in turn enhances consumer loyalty. This study aims to examine the influence of brand experience and brand trust on brand loyalty, mediated by brand love. The population in this study consists of Eiger consumers in Purworejo Regency. A sample of 150 respondents was selected using a purposive sampling technique. Data were collected through a questionnaire using a Likert scale. Data analysis was conducted using SmartPLS 4.0 with the Structural Equation Modeling (SEM) approach. The findings show that brand experience, brand trust, and brand love have a positive and significant effect on brand loyalty; brand experience and brand trust have a positive and significant effect on brand love; brand love provides complementary mediation in the relationship between brand experience and brand loyalty; and brand love also provides complementary mediation in the relationship between brand trust and brand loyalty.